A perspective on the major light-harvesting complex dynamics under the effect of pH, salts, and the photoprotective PsbS protein - Navakoudis, Eleni; Stergiannakos, Taxiarchis; Daskalakis, Vangelis (My University, 2023)
The photosynthetic apparatus is a highly modular assembly of large pigment-binding proteins. Complexes called antennae can capture the sunlight and direct it from the periphery of two Photosystems (I, II) to the core reaction centers, where it is converted into chemical energy. The apparatus must cope with the natural light fluctuations that can become detrimental to the viability of the photosynthetic organism. Here we present an atomic scale view of the photoprotective mechanism that is activated on this line of defense by several photosynthetic organisms to avoid overexcitation upon excess illumination. We provide a complete macroscopic to microscopic picture with specific details on the conformations of the major antenna of Photosystem II that could be associated with the switch from the light-harvesting to the photoprotective state. This is achieved by combining insight from both experiments and all-atom simulations from our group and the literature in a perspective article.
Keywords: Dissipating state; LHCII; Light-harvesting complex; Molecular dynamics; NPQ; Photoprotection